CHANGE IN MRNA EXPRESSION OF SIRTUIN-2 AND SIRTUIN-3 IN RHEUMATOID ARTHRITIS - Kara, M.; Yolbas, S.; Yildirim, A.; Gundogdu, B.; Ozgen, M.; Sahin, C.; Koca, S. S. (Bmj Publishing Group, 2014)
[Abstract Not Available]
15th Annual European Congress of Rheumatology (EULAR) -- JUN 11-14, 2014 -- Paris, FRANCE
Keywords: Suppresses Inflammatory Responses; Collagen-Induced Arthritis